Preimplantation genetic testing in two Danish couples affected by Peutz–Jeghers syndrome. (4th March 2023) - Byrjalsen, Anna; Roos, Laura; Diemer, Tue; Karstensen, John Gásdal; Løssl, Kristine; Jelsig, Anne Marie
Abstract: Background: Guidelines from the European Hereditary Tumor Group as well as The Danish National Guidelines for Peutz–Jeghers Syndrome (PJS) state that both prenatal diagnosis and preimplantation genetic testing for monogenic disorders (PGT-M) should be offered to patients with PJS. However, only a few cases resulting in viable pregnancies have been published. Objective: We present two cases of PJS patients going through PGT-M for PJS. We highlight the awareness of this possibility and discuss the technical and ethical challenges of performing PGT-M for PJS. Methods and results: Case 1: A 36-year-old male with PJS and his partner were referred for genetic counseling. The patient carried a pathogenic de novo variant in STK11 . After a terminated pregnancy of a fetus carrying the same pathogenic variant, microsatellite polymorphic marker analysis was established, and the patient was offered PGT-M. The female partner of the patient gave birth to a healthy boy after five years of fertility treatment. Case 2: A 35-year-old female with PJS and her partner were referred for genetic counseling. She carried an inherited pathogenic STK11 variant. The couple was offered PGT-M. Genetic testing of the embryos was performed using microsatellite polymorphic markers. After two rounds of oocyte extraction a blastocyst predicted not to be affected by PJS was identified. The blastocyst was transferred; however, this did not result in a viable pregnancy. Conclusions: PGT-M can be offered to patients with PJS. The process may be long and filled with ethical dilemmas requiring patients to be motivated and persistent.